CRISPR-Cas9-Mediated Mutagenesis of the Rubisco Small Subunit Family in Nicotiana tabacum - Donovan, Sophie; Mao, Yuwei; Orr, Douglas J.; Carmo-Silva, Elizabete; McCormick, Alistair J. (Frontiers in Genome Editing, 2020)
Engineering the small subunit of the key CO2-fixing enzyme Rubisco (SSU, encoded by rbcS) in plants currently poses a significant challenge, as many plants have polyploid genomes and SSUs are encoded by large multigene families. Here, we used CRISPR-Cas9-mediated genome editing approach to simultaneously knock-out multiple rbcS homologs in the model tetraploid crop tobacco (Nicotiana tabacum cv. Petit Havana). The three rbcS homologs rbcS_S1a, rbcS_S1b and rbcS_T1 account for at least 80% of total rbcS expression in tobacco. In this study, two multiplexing guide RNAs (gRNAs) were designed to target homologous regions in these three genes. We generated tobacco mutant lines with indel mutations in all three genes, including one line with a 670 bp deletion in rbcS-T1. The Rubisco content of three selected mutant lines in the T1 generation was reduced by ca. 93% and mutant plants accumulated only 10% of the total biomass of wild-type plants. As a second goal, we developed a proof-of-principle approach to simultaneously introduce a non-native rbcS gene while generating the triple SSU knockout by co-transformation into a wild-type tobacco background. Our results show that CRISPR-Cas9 is a viable tool for the targeted mutagenesis of rbcS families in polyploid species and will contribute to efforts aimed at improving photosynthetic efficiency through expression of superior non-native Rubisco enzymes in plants.